Compliance with Food Safety Laws in Germany: Food Businesses in Berlin. (27th July 2018) - Fietz, Anica; Bavorová, Miroslava; Grüner, Sven; Hirschauer, Norbert
Abstract : In this article we explore how variables associated both with material temptations (economic incentives that foster rule breaking) and nonmaterial behavioral determinants (protective factors that shield people from rule breaking) are linked to compliance with food laws. The object of the study is to examine food businesses in the ready‐to‐eat industry in three districts of the German capital, Berlin. We collected data on compliance behavior and its potential drivers via an anonymous postal survey in 2014. Accounting for the data structure, we used a generalized ordered logit regression to model the relationship between the presumed behavioral drivers and compliance. One crucial finding is that a feeling of embarrassment if relevant others were to learn about noncompliance is positively related to compliance. The same holds for the internalized approval of food laws and their enforcement (acceptance of rules).